Reformed Protestantism and the Origins of Modern Environmentalism - Northcott, Michael S. (Philosophia reformata, 2018)
The question I investigate in this essay is why it was individuals and regions with a Reformed Protestant religious background—rather than, say, Roman Catholic, Eastern Orthodox, Buddhist, or Taoist—which pioneered environmental campaigns and efforts to set aside national parks and rare species for conservation. Subsidiary questions discussed are two: (1) What might be the roots of an affinity between Protestantism and an ecological orientation to the world? (2) If there was this affinity in the nineteenth-century origins of ecological conservation, why is it not more widely acknowledged in contemporary scholarship and in the public mind?